OPTIMALISASI KINERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH KOTA SEMARANG - Sri Hindah Pudjihastuti; Haves Ardhani (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2013)
The aim of this research is to find out and analyzing the influence of motivation against the employee performance of badan kepegawaian city semarang and to know and analyzing the influence of discipline against the employee performance of Badan Kepegawaian Daerah Kota Semarang. A method of research used in the sample of the population is a method of census against 65 respondents derived from the staff of Badan Kepegawaian Daerah Kota Semarang overall, to be used as a sample of but only 64 a questionnaire that back and analyzed. A method of collecting data used namely a questionnaire that is supported by observation, informal interview and documentation. The result showed motivation influential positively and significantlyaffect the performance of civil servants. Variable discipline shows that there are a positive influence and significant on the performance of civil servants Motivation have leverage our dominant against the employee performance than by discipline. Variable motivation and discipline can explain variation variable the employee performance 56,6 %, amounting to while 43,4 % described by another variable outside modeled on standard trust 95 % ( sig. 5 % ).Keywords: Motivation, Discipline, Employee Performance